Transition markers in Qatari university students' argumentative writing: A cross-linguistic analysis of L1 Arabic and L2 English - Abdelhamid M. Ahmed (16810680) (2023)
The current cross-linguistic study compares university students' use of transition markers (addition, compare/contrast, and consequence markers) in their L1 Arabic and L2 English argumentative writing. It also explores students' metalinguistic understanding of transition markers (TMs) through writing conversation interviews. We analysed the Qatari Corpus of Argumentative Writing (QCAW), which comprises 390 texts in L1 Arabic and L2 English written by the same Qatari undergraduate students. Using Hyland's (2005) model of metadiscourse, the findings revealed that frequencies of transition marker use among less proficient L2 English writers were closer to L1 Arabic. Based on the results of a writing proficiency test, low-proficiency students transferred overt strategies to signal transitions, supported by the interview findings. Interestingly, students with an average L2 English proficiency exhibited a greater variety in TMs. In contrast, higher-proficiency writers tended to use more complex and subtler means to indicate textual transitions. The students used TMs for different purposes. Lack of knowledge and writing under controlled conditions inhibited some participants from using TMs. The paper concludes with pedagogical implications for teaching and assessing TMs. Other Information Published in: Ampersand License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.amper.2023.100110